2021
DOI: 10.1029/2020jb021321
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Compaction of Crustal Analogs Made of Sintered Glass Beads: The Influence of Porosity and Grain Size

Abstract: The fundamentals of our understanding of the mechanical compaction of porous rocks stem from experimental studies. Yet, many of these studies use natural materials for which microstructural parameters are intrinsically coupled, hampering the diagnosis of relationships between microstructure and bulk sample behavior. To probe the influence of porosity and grain size on the mechanical compaction of granular rocks, we performed experiments on synthetic samples prepared by sintering monodisperse populations of gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 122 publications
1
35
2
Order By: Relevance
“…Data of this nature for sandstone and limestone highlight that, although porosity exerts an importance influence on the stress conditions required for the brittle-ductile transition and shear-enhanced compaction, other microstructural parameters such as grain size also play a role (e.g. Wong and Baud 2012; see also Carbillet et al 2021). Porosity also exerts an important control on these critical stresses for volcanic rocks: the switch from brittle to ductile behaviour and the compactive yield cap are, in general, at higher stress values for rocks with a lower porosity (Fig.…”
Section: Ductile Triaxial Deformation Experimentsmentioning
confidence: 99%
“…Data of this nature for sandstone and limestone highlight that, although porosity exerts an importance influence on the stress conditions required for the brittle-ductile transition and shear-enhanced compaction, other microstructural parameters such as grain size also play a role (e.g. Wong and Baud 2012; see also Carbillet et al 2021). Porosity also exerts an important control on these critical stresses for volcanic rocks: the switch from brittle to ductile behaviour and the compactive yield cap are, in general, at higher stress values for rocks with a lower porosity (Fig.…”
Section: Ductile Triaxial Deformation Experimentsmentioning
confidence: 99%
“…The synthetic samples used to conduct this work were prepared by the viscous sintering of spherical glass beads, following the method presented in Carbillet et al. (2021). When heated above their glass transition temperature, the beads act as liquid droplets and begin a time‐dependent coalescence driven by interfacial tension, a process that progressively decreases the porosity of the system (Wadsworth et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The influence of the mean grain size on the hydromechanical behavior of porous rocks has been explored in the laboratory using natural (Brace, 1961; Fredrich et al., 1990; Guyon et al., 1987; Olsson, 1974; Wasantha et al., 2015) and synthetic rocks (Carbillet et al., 2021), and using numerical modeling (Cil & Buscarnera, 2016; Ghazvinian et al., 2014; Yu et al., 2018). For porous sandstones, experimental laboratory studies using correlation analysis reported that grain size has a significant influence on uniaxial compressive strength, where the larger the grain size the lower the strength (Bell & Culshaw, 1998; Fahy & Guccione, 1979; Wasantha et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In subsequent studies, irreversible compaction was modeled on the basis of viscous [3][4][5] and visco-plastic rheology [6][7][8], including taking into account temperature effects [9] and large deformations [10]. It should be noted that the theoretical results only partially describe the available experimental data [11][12][13]. Recent studies have shown that rock compaction occurs at all stress levels from the very beginning of compression, i.e.…”
mentioning
confidence: 99%